A leitura em livros didáticos do ensino fundamental e a formação para o leitor crítico literário - Silva, Rosenil Gonçalina dos Reis e (2015)
This research aims to discuss the formation of readers, focusing on the activities of text reading in the genres of literary sphere. We chose do so because we consider reading as fundamental in the social formation of the individual, a prerequisite for citizenship. Literature also helps in the formation of man, because it establishes itself as a symbolic and ideological phenomenon, susceptible to multiple interpretations, which collaborates in promoting its autonomy and to a critical reading of the various problems that arise in society's everyday life. Thus, we selected, for our analysis, only the literary genres present in the reading activities of a collection of textbooks in Portuguese Language, titled "Vontade de Saber Português", by the authors Rosemeire Alves and Tatiane Brugnerotto, approved by the 2014 PNLD - Programa Nacional do Livro Didático (National Textbook Program) - selected from of its choice and usage in one of the largest public schools in Cuiabá, Mato Grosso, in number of students enrolled, a total of 2,300. Our goal was to first identify which genres of the literary sphere are present in each volume of the collection, then, to check what are the activities that specifically address reading and, finally, to verify which reading skills these activities mobilize, and, if, for a fact, they contribute or not to the development of the reader skills of the student. For that, we turn to some assumptions of the enunciative-discoursive theory of Bakhtin and the Circle, that, in this context, allied to other contributions, such as critical literacy and fundamentals of Vygotsky's conception for the understanding of aspects of language, ideology and interaction, which influence in the learning and constitution of social subjects, as well as Freire's, which have inspired the studies of critical literacy. This is a research of documental analysis, of qualitative and dialogical approach. For methodological purposes, we conducted a quantitative survey that provided information for qualitative analysis. Data analysis revealed that the incidence of texts in genres of thr literary sphere is unrepresentative, under two aspects. First, in relation to the total amount of texts in genres of other spheres, and secondly, in relation to the quantity of those used for reading activities. In addition, the educational treatment given to reading activities does not favor the mobilization of reading capabilities capable of fostering the student's autonomy, and it does not promote a transforming education. Thus, in general, the collection contributes little to the formation of literary and critical literacy of elementary school students in the public schools that use it. We hope that this work can contribute to reflections on the need for a reader formation in the school context, with particular emphasis on critical literacy in various school levels, supporting the development of specific skills for reading not only genres of the literary sphere, but in other spheres of human activity.